Proceedings of the Fourth Workshop on Natural Language Processing and Computational Social Science 2020
DOI: 10.18653/v1/2020.nlpcss-1.11
|View full text |Cite
|
Sign up to set email alerts
|

Is Wikipedia succeeding in reducing gender bias? Assessing changes in gender bias in Wikipedia using word embeddings

Abstract: Large text corpora used for creating word embeddings (vectors which represent word meanings) often contain stereotypical gender biases. As a result, such unwanted biases will typically also be present in word embeddings derived from such corpora and downstream applications in the field of natural language processing (NLP). To minimize the effect of gender bias in these settings, more insight is needed when it comes to where and how biases manifest themselves in the text corpora employed. This paper contributes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…13 The editors' community is consequently tackling this problem and fighting the gender gap. As recently shown by Schmahl et al (2020), these efforts pay off and not only more biographies about women are being added, but also NLP models such as word embeddings trained on Wikipedia articles are exhibiting less stereotypical biases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The editors' community is consequently tackling this problem and fighting the gender gap. As recently shown by Schmahl et al (2020), these efforts pay off and not only more biographies about women are being added, but also NLP models such as word embeddings trained on Wikipedia articles are exhibiting less stereotypical biases.…”
Section: Discussionmentioning
confidence: 99%
“…In their following analysis, Wagner et al (2016) showed that gender inequalities can be observed also on other dimensions, e.g., women have to be more notable to have their biographies than men. These patterns occurring in Wikipedia have been shown to directly influence NLP models, such as word embeddings (Schmahl et al, 2020) or relation extraction (Gaut et al, 2020).…”
Section: Introductionmentioning
confidence: 99%